Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1088/1741-2552/ab0678
|View full text |Cite
|
Sign up to set email alerts
|

Cortical recruitment and functional dynamics in postural control adaptation and habituation during vibratory proprioceptive stimulation

Abstract: Objective. Maintaining upright posture is a complex task governed by the integration of afferent sensorimotor and visual information with compensatory neuromuscular reactions. The objective of the present work was to characterize the visual dependency and functional dynamics of cortical activation during postural control.Approach. Proprioceptic vibratory stimulation of calf muscles at 85 Hz was performed to evoke postural perturbation in open-eye (OE) and closed-eye (CE) experimental trials, with pseudorandom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 69 publications
(117 reference statements)
1
23
0
10
Order By: Relevance
“…There are two main limitations to note from this methodology. Firstly, while it remains possible that the onset of habituation or fatigue may differ subject-to-subject, previous studies have shown that ant-post and lat torque variations during OE and CE trials reach a consistent minimum around 150-200 seconds following incident stimuli, corresponding with P3 in the present work [3], [10]. Nevertheless, further investigation into quantitative indicators for the measurement of cortical habituation is recommended.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…There are two main limitations to note from this methodology. Firstly, while it remains possible that the onset of habituation or fatigue may differ subject-to-subject, previous studies have shown that ant-post and lat torque variations during OE and CE trials reach a consistent minimum around 150-200 seconds following incident stimuli, corresponding with P3 in the present work [3], [10]. Nevertheless, further investigation into quantitative indicators for the measurement of cortical habituation is recommended.…”
Section: Discussionmentioning
confidence: 67%
“…Postural sway was recorded to obtain normalized SPL values over five experimental periods, which were then utilized to classify postural adaptation and postural habituation as differences in ASP between specific recording periods. In this regard, adaptation was defined as the difference between P1 and QS periods, in accordance with extant postural perturbation literature [3], [10], [12]. However, normalized SPL was used to define postural habituation, where P1 ASP values were subtracted from the period with the lowest mean SPL to avoid the influence of time-dependent variations such as fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations